Παλαιοπεριβαλλοντική εξέλιξη της λιμνοθάλασσας του Κίτρους Πιερίας, ΒΔ Θερμαϊκός Κόλπος - Δημητράκος, Α.Σ.; Βουβαλίδης, Κ.; Συρίδης, Γ.; Αλμπανάκης, Κ. (Bulletin of the Geological Society of Greece, 2011)
This paper deals with the palaeoenvironmental evolution of the Kitros Pierias Lagoon, located at the west coastline of the Thermaikos Gulf, during the upper Holocene. In addition, the palaeoenvi-ronmental units distinguished in the study area were correlated with the Holocene sea level rise in Thermaikos Gulf. The study is based on the sedimentological and stratigraphical analysis of a core 9.5 m long. Sedimentological and palaeontological analysis was carried out in all selected core sam-ples. The determination of the lithophases and biophases allowed the estimation of the stratigraphy-cal units, the interpretation of the geomorphological evolution and the characterization of the palaeo-environmental conditions. According to the results, we can conclude that the area under investigation was a transitional lagoonal environment, semi-enclosed at its initial stage progressively transformed to an isolated sallow basin. The formation of the semi-enclosed lagoon has been commenced after the conclusion of the rapid phase of sea level rise i.e. 6,000 BP years. Finally, the gradual isolation of the lagoon is attributed to low rate of the sea level rise e.g. over the past 4,000 years..